How the USA and China Can Benefit From The Conflict of Ukraine and Russia - Komiljonov Javokhir (Cita Konsultindo Research Center, 2022)
The study focuses on the trends during the historical relations of Ukraine and Russia, changes before the war and after. While the war is giving serious influence on the world economy, politics and world peace, it is clear that almost every country is having either benefits or damages, and more probably both at the same time in the globalized world. However, the research’s topic demonstrates the benefits of the US and China from the alterations after the war happened. Still, the word “benefits” can be defined widely which at the same time leads to a misunderstanding if considered every possible benefit. The remaining unanswered questions are “what if they are different benefits for each country” and “how can the case be possible to study and compare?”. Having deeper analysis and contrasting the fields and the ways in which the two states can mostly benefit, the study shows how the war influenced the world countries differently in an example of Chin and the US, and their relations during the time of war as well as ongoing sanctions.